ANALYSIS THE DEVELOPMENT REALIZATION OF INCOME TAX (PPH) AND VALUE ADDED TAX (PPN) REVENUE AT KPP PRATAMA SOREANG FOR THE YEARS 2018-2022 - Chyintia Malau; Lorina Siregar Sudjiman (Jurnal Ekonomi, 2023)
This research aims to analyze the development of tax revenue acceptance, its effectiveness, and the supporting, inhibiting factors, as well as solutions for the realization of income tax (PPh) and value-added tax (PPN) at the Soreang Tax Office from 2018 to 2022. The data used in this research are secondary data. The research findings indicate that the realization of income tax and value-added tax still fluctuates, meaning that there are years when the revenue target is achieved and others when it is not. This is due to various factors, such as economic conditions, taxpayer compliance, consumption levels, and taxpayer resources in the Soreang Tax Office.